Elements, Transformations, and Strategies that Intervene in the Adaptation to the University from the Viewpoint of Freshmen and Regular Students at Universidad Nacional - Valverde Lopez, Lizeth (2022)
This paper collects the perceptions of first-year and advanced college students at Universidad Nacional (UNA) of Costa Rica. The main objective of the inquiry was to identify the elements and transformations that are involved in the adaptation of college students to demonstrate strategies to promote success in the adaptation process to the college life from the student’s perspective. This study has been done based on Participatory Action Research with 14 students at UNA in synchronous and asynchronous meetings; the collected data were categorized through a writing process of four layers: literal transcription of the meetings and classification of the information, highlighting the data based on purposes, critical and reflective interpretation, as well as the link with the authors. It was found, among the main transformations experience, that supporting networks are key elements that take part in the adaptation to university life as well as knowing the university and its related concepts. Spaces for relief and support for first-year students were highly recommended according the obtained findings.